Jejak Karawitan dalam Kakawin Sumanasantaka - Hendra Santosa; Dyah Kustiyanti; I Komang Sudirga (LP2M ISBI Bandung, 2018)
ABSTRACT Kakawin Sumanasantaka (Death Because Sumanasa Flowers) is one of sources in searching musical terms from about 22 manuscripts in early Old Javanese literature. This article is part of the research entitled